Impact of channel bar form and grain size variability on estimated stranding risk of juvenile brown trout during hydropeaking. Issue 12 (28th March 2014) - Hauer, Christoph; Unfer, Günther; Holzapfel, Patrick; Haimann, Marlene; Habersack, Helmut
ABSTRACT Hydropeaking leads to artificial fluctuations in discharge and corresponding water levels with pronounced dewatering areas between base and peak flow along gravel bars and channel banks. In the present study, 16 hydropeaking reaches in Austria were investigated to assess possible differences in the estimated stranding risk for young of the year brown trout according to different gravel bar types and differences in microtopography roughness. Based on hydrodynamic‐numerical modelling, a predictive habitat modelling approach was implemented in the study design. Accompanied by grain size sampling along the various channel bars, a conceptual stranding risk model (SRM) was developed. The results showed that a high variability in estimated stranding risk exists for the tested sites considering discharge ratios of 1:3, 1:5 and 1:10. With respect to the discussion of establishing legal thresholds for ramping ratios in discharge, it was documented that, exemplarily, a discharge ratio base flow/peak flow of 1:5 (winter base flow conditions) could cause minor differences in the spatial extent of dewatering areas and the related estimated stranding risk for juvenile brown trout compared to a ratio of 1:2 for summer base flow conditions. Microtopographic roughness was addressed due to sampling and analysis of grain size distributions. Statistical testing of grain size distributions revealed significant differences between the surface material compositions of the investigated gravel bars. Those differences are evident, particularly for the coarser fraction (d90), which is important as cover for young of the year brown trout. These aspects of grain size in habitat use and hydraulics have been addressed in the conceptual SRM. The results showed that point bar morphology, in particular, was less sensitive to the risk of stranding compared to, for example, alternating gravel bars. Considering the multiple pressures for alpine rivers, the improvement of structural features due to bar formation and related self‐forming processes is discussed as a possible alternative for future mitigation measures to reduce the negative impacts of hydropeaking. Copyright © 2014 John Wiley & Sons, Ltd.